2005
DOI: 10.1021/es049871p
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Investigation of Ultrafine Coal Fly Ash Particles

Abstract: Ultrafine (<100 nm) ash particles in three coal fly ashes (CFA) produced by the combustion of three U.S. coals have been examined by high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDS), and electron diffraction. These ultrafine particles, either as primary ash particles derived directly from coal minerals or as secondary products of decomposition and vaporization-condensation processes, show quite different morphologies, compositions, and microstructures as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 27 publications
9
82
0
Order By: Relevance
“…Ti-Al-Fe, Fe-Si-Al, Ti-Si-Al, and Al-Mg-Fe are the major three-element categories (Chen et al, 2005). Our investigation also found the very similar combination of ultrafine coal fly ash particles.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Ti-Al-Fe, Fe-Si-Al, Ti-Si-Al, and Al-Mg-Fe are the major three-element categories (Chen et al, 2005). Our investigation also found the very similar combination of ultrafine coal fly ash particles.…”
Section: Resultssupporting
confidence: 76%
“…These nano-particles in Steubenville showed very similar morphology and elemental composition of individual particles that were collected in Detroit. Chen et al (2005) previously characterized and documented ultrafine coal fly ash particles by using high-resolution transmission electron microscopy. Their study reported that a combination of Ti-Al-Fe ultrafine particles has been found in Western Kentucky coal fly ash most frequently, and oxides of Fe, Ti, and Ca constitute the major single-element categories, and…”
Section: Resultsmentioning
confidence: 99%
“…From a toxicological standpoint, the smallest particles are of the greatest concern when ash is handled at landfill disposal sites (i.e. in transport and disposal, particularly in stormy weather conditions), and some researches have reported risks to workers with prolonged exposure to ash (Chen et al, 2005;Cprek et al, 2007).…”
Section: Particle Size Distribution Of Metals In the Cyclone Fly Ashmentioning
confidence: 99%
“…All three samples also showed aggregates of carbonaceous particles with the size of 20-50 nm. Similarly, the carbonaceous soot particles were mixed or coated with multielement inorganic species in some cases [20]. Also, Hower et al used a combination of HR-TEM, scanning transmission electron microscopy (STEM) and electron energy-loss spectroscopy (EELS) to investigate fly ashes obtained from the combustion of an eastern Kentucky coal.…”
Section: Microscopy Techniquesmentioning
confidence: 99%